Daily field checking list by Walter Rosene, October 7, 1933 - Rosene, Walter M., Sr., 1880-1941et al; Iowa Ornithologists' Unionet al
Bird checklist dated October 7, 1933. This checklist was used by Walter Rosene to record birds sighted around Yell Township, Boone County between 9:00 and 12:00. Plustek--flatbed